A high-performance alkali metal-modified CuFeZr catalyst material and preparation method thereof
By preparing alkali metal modified CuFeZr catalytic materials, using multiple steps to form nanoscale copper/ferrooxide nanocrystals and copper-ferroalloy/interface species, the problem of unstable activity of copper-ferro-based catalysts is solved, and the effect of high selectivity catalytic reduction of CO2 to low-carbon alcohol at low temperatures is achieved.
Patent Information
- Application Number
- CN202111390433.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-11-18
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2041-11-18
AI Technical Summary
The existing copper-iron-based catalysts are unstable in reducing atmospheres, prone to inactivation, and the exposed active area is reduced at high temperatures, resulting in a rapid reduction in catalytic activity.
By preparing high-performance alkali metal modified CuFeZr catalytic materials, a multi-step reaction method is adopted, including ultrasonic dissolution of zirconium salt, hydrothermal reaction, ultrasonic dispersion, precipitation and calcination, nanoscale copper/ferrooxide nanocrystals and copper-ferroalloy/interface species, enhancing the stability of the active species.
The catalytic reduction of CO2 at low temperature conditions is achieved to synthesize low-carbon alcohols, which improves catalytic activity and thermal stability and reduces preparation costs.
Smart Images

Figure BDA0003362576810000111 
Figure BDA0003362576810000121 
Figure BDA0003362576810000122
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalytic materials, and particularly relates to a high-performance alkali metal-modified CuFeZr catalytic material and a preparation method thereof. Background Art
[0002] Oxide-based porous materials are good carriers in the field of catalysis, but the preparation method of high-performance low-carbon alcohol synthesis catalytic materials still needs further exploration. Copper-iron-based materials are widely used in catalytic reactions such as carbon dioxide hydrogenation to synthesize methanol and low-carbon alcohols, Fischer-Tropsch reaction, etc. due to their unique redox properties and high catalytic activity.
[0003] It is generally believed that the catalytic reaction mainly takes place on the copper surface and the Cu-Fe interface. However, copper-based catalysts are prone to become metallic copper due to their extremely unstable microstructure of active copper species in a reducing atmosphere. They are also prone to sintering at high temperatures, causing their exposed active area to decrease rapidly, resulting in a rapid decrease in catalytic activity or even inactivation.
[0004] Metals (such as copper, iron, etc.) highly dispersed in porous oxide materials with high surface areas have been proven to be good redox reaction catalysts. Copper oxide and iron oxide have relatively high thermal stability. At the same time, because they are active components or active additives for catalytic reactions such as synthesis gas and carbon dioxide hydrogenation to synthesize methanol and low-carbon alcohols, adding copper oxide, iron oxide and other metals to amorphous zirconium oxide with a high specific surface area can form nano-scale copper nanocrystals and rich alloy / interface species, thereby increasing the stability of active species and the ability of the catalyst to catalyze the dissociation of hydrogen and activate carbon dioxide, enhancing the yield and selectivity of low-carbon alcohols, and facilitating the hydrogenation reaction of carbon dioxide, thereby preparing a high-performance CO2 hydrogenation to synthesize low-carbon alcohol catalytic material.
[0005] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention and should not be regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art. Summary of the invention
[0006] In order to solve the above problems, the present invention provides a method for preparing a high-performance alkali metal-modified CuFeZr catalytic material, which has the advantages of low preparation cost, simple and safe operation, short reaction cycle, good product repeatability, etc.; the high-performance alkali metal-modified CuFeZr catalytic material prepared by the method has the advantages of low cost, high catalytic activity, high thermal stability, etc., can catalytically reduce CO2 to synthesize low-carbon alcohols with high selectivity under relatively low temperature conditions, and can be used in the fields of material research and catalytic hydrogenation of carbon dioxide to synthesize low-carbon alcohols.
[0007] The present invention is achieved by adopting the following technical solutions:
[0008] The preparation method of high-performance alkali metal-modified CuFeZr catalyst material comprises the following steps:
[0009] S1, adding zirconium salt to ethanol solvent, dissolving by ultrasonication, and then adding propylene oxide to carry out a first contact reaction to obtain solution I;
[0010] S2, subjecting solution I to a hydrothermal reaction, and drying and crushing the resulting material to obtain amorphous zirconium oxide;
[0011] S3, adding amorphous zirconium oxide into water, dispersing by ultrasonic, adding metal copper salt, performing a second contact reaction, and obtaining solution II;
[0012] S4, adding a precipitant aqueous solution to solution II to carry out a third contact reaction, and after the reaction is completed, the obtained material is centrifuged, dried, crushed, and calcined;
[0013] S5, subjecting the obtained solid to a fourth contact reaction with a metal iron salt to obtain a solution III;
[0014] S6, subjecting the solution III to a fifth contact reaction with a precipitant, and after the reaction is completed, centrifuging, drying, and crushing the obtained material;
[0015] S7, the obtained material is subjected to a sixth contact reaction with an alkali metal salt, and after rotary evaporation of water, the obtained material is crushed and calcined to obtain a high-performance alkali metal-modified CuFeZr catalytic material.
[0016] In a preferred embodiment, in step S1, the ultrasonic dissolution is performed at a frequency of 40-60 KHz for 25-40 min; in a further preferred embodiment, the ultrasonic dissolution is performed at a frequency of 50 KHz for 30 min;
[0017] In a preferred embodiment, in step S1, the zirconium salt may be one of zirconium nitrate, zirconium oxychloride, zirconium chloride and zirconium sulfate; the molar ratio of propylene oxide and zirconium salt calculated as Zr element is (1.5-2.5):1; in a further preferred embodiment, the molar ratio of propylene oxide, ethanol and zirconium nitrate calculated as Zr element is (1.5-2.5):(60-70):1.
[0018] In a preferred embodiment, in step S1, the conditions of the first contact reaction are: temperature of 10-40° C. and time of 0.05-1 h.
[0019] In a preferred embodiment, in step S1, the first contact reaction is carried out under stirring conditions at a stirring rate of 50-500 rpm; in a further preferred embodiment, the first contact reaction is carried out under stirring conditions at a stirring rate of 350-450 rpm.
[0020] In a preferred embodiment, in step S2, the temperature of the hydrothermal reaction is 100-200° C. and the time is 15-25 h.
[0021] In a preferred embodiment, in step S3, the conditions of the second contact reaction are: temperature of 10-40° C. and time of 0.05-10 h.
[0022] The copper salt may be any one of copper nitrate, copper sulfate, copper acetate, and copper chloride;
[0023] In terms of mass ratio, the usage ratio of the metal copper salt in terms of Cu element and the amorphous zirconium oxide in terms of zirconium oxide is (0.2-0.3):1;
[0024] In a preferred embodiment, in step S3, the second contact reaction is carried out under stirring conditions at a stirring rate of 50-500 rpm; in a further preferred embodiment, the second contact reaction is carried out under stirring conditions at a stirring rate of 350-450 rpm.
[0025] In a preferred embodiment, in step S4, the conditions of the third contact reaction are: temperature of 70-90° C. and time of 0.1-10 h.
[0026] The precipitant can be any one of ammonium carbonate, ammonium bicarbonate, potassium carbonate, potassium bicarbonate, sodium carbonate, sodium bicarbonate, sodium hydroxide, potassium hydroxide, and ammonia water;
[0027] In terms of molar ratio, the ratio of the precipitant to the metal copper salt in terms of Cu element is 1-3:1;
[0028] In a preferred embodiment, in step S5, the conditions of the fourth contact reaction are: temperature of 10-40° C. and time of 0.1-10 h.
[0029] The iron salt may be any one of ferric nitrate, ferric acetate, ferric sulfate, and ferric chloride;
[0030] The mass ratio of the metal iron salt calculated as Fe element to the copper zirconium material calculated as copper zirconium oxide is (0.1-0.2):1;
[0031] In a preferred embodiment, in step S6, the fifth contact reaction is carried out under stirring conditions at a stirring rate of 50-500 rpm; in a further preferred embodiment, the fifth contact reaction is carried out under stirring conditions at a stirring rate of 350-450 rpm.
[0032] In a preferred embodiment, in step S6, the conditions of the fifth contact reaction are: temperature of 70-90° C. and time of 0.1-10 h.
[0033] The precipitant can be any one of ammonium carbonate, ammonium bicarbonate, potassium carbonate, potassium bicarbonate, sodium carbonate, sodium bicarbonate, sodium hydroxide, potassium hydroxide, and ammonia water;
[0034] In terms of molar ratio, the ratio of the precipitant to the metallic iron salt in terms of Fe element is 1-3:1;
[0035] In a preferred embodiment, in step S7, the conditions of the sixth contact reaction are: temperature of 10-40° C. and time of 0.1-10 h.
[0036] The alkali metal salt may be any one of potassium carbonate, sodium carbonate, and cesium carbonate;
[0037] The molar ratio of the alkali metal salt calculated as the alkali metal element to the amorphous zirconium oxide calculated as the Zr element is (0.1-0.25):1;
[0038] In a preferred embodiment, in step S7, the sixth contact reaction is carried out under stirring conditions at a stirring rate of 50-500 rpm; in a further preferred embodiment, the sixth contact reaction is carried out under stirring conditions at a stirring rate of 350-450 rpm.
[0039] In a preferred embodiment, in steps S2 and S6, the drying conditions are as follows: the temperature is 40-80°C and the time is 2-24h;
[0040] Preferably, in step S4, the drying conditions include: temperature of 40-80°C, time of 2-24h; the calcination conditions include: temperature of 300-500°C, time of 0.5-8h.
[0041] In a preferred embodiment, in step S7, the conditions for rotary evaporation include: temperature of 40-80°C, vacuum degree of -0.08 to -0.1, and time of 2-6 hours; the conditions for calcination include: temperature of 300-500°C, and time of 3-10 hours.
[0042] The beneficial effects of the present invention are:
[0043] 1. The preparation method of the present invention has the advantages of low preparation cost, simple and safe operation, short reaction cycle, good product reproducibility, etc.
[0044] 2. The high-performance alkali metal-modified CuFeZr catalytic material prepared by the preparation method of the present invention can provide nano-scale copper / iron oxide nanocrystals, or copper-iron alloy / interface species, which can increase the stability of active species, the catalyst's catalytic hydrogen dissociation activity and the ability to activate carbon dioxide, and is beneficial to the selective catalytic carbon dioxide reduction reaction.
[0045] 3. The high-performance alkali metal-modified CuFeZr catalytic material prepared by the preparation method of the present invention has the advantages of low cost, high catalytic activity, high thermal stability, etc. It can catalyze the reduction of CO2 to synthesize low-carbon alcohols with high selectivity under low temperature conditions, and can be used in the fields of material research and catalytic hydrogenation of carbon dioxide to synthesize low-carbon alcohols. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0047] Figure 1 It is the XRD spectra of the CuFeZr catalytic material prepared in Example 1 of the present invention and the high-performance alkali metal modified CuFeZr catalytic materials prepared in Examples 2-6. DETAILED DESCRIPTION
[0048] The technical scheme in the embodiment will be described clearly and completely below in conjunction with the accompanying drawings in the embodiment of the present invention. Obviously, the described embodiment is only a part of the embodiment of the present invention, not all of the embodiments. Based on the embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0049] Example 1
[0050] A method for preparing a CuFeZr catalyst material comprises the following steps:
[0051] S1, at 25° C., 5.999 g of zirconium nitrate pentahydrate was dissolved in ethanol to obtain a mixture, and after ultrasonic dissolution for 30 min at a frequency of 50 KHz, propylene oxide was added to carry out a first contact reaction for 2 min to obtain a solution I;
[0052] S2, performing a hydrothermal reaction at 150°C for 20 hours, drying the obtained solid sol at 60°C for 24 hours, and then drying at 200°C for 3 hours before crushing to obtain a powdery amorphous zirconium oxide solid; in terms of molar ratio, the amount of zirconium nitrate pentahydrate: ethanol: propylene oxide is 1:60:1.5;
[0053] S3, at 25°C, 0.3 g of amorphous zirconium oxide solid is dispersed in 50 mL of water under ultrasonic conditions at a frequency of 50 KHz for 15 min to obtain a zirconium oxide aqueous dispersion with a mass concentration of 6 g / L; the water is deionized water;
[0054] S4, at 25°C, potassium carbonate is dissolved in water to form a potassium carbonate aqueous solution with a mass concentration of 9.6 g / L;
[0055] S5, taking the zirconium oxide aqueous dispersion, adding 0.2215 g of copper nitrate, stirring at 400 rpm for a second contact reaction at 25° C. for 1 hour; the molar ratio of potassium carbonate to copper nitrate in terms of Cu is 1.5:1;
[0056] S6, adding the potassium carbonate aqueous solution at 80°C and stirring for a third contact reaction for 3 hours; after the reaction is completed, the obtained material is fully washed and centrifuged at 6000-8000 rpm, the precipitate obtained after centrifugation is dried at 60°C for 12 hours, crushed, and calcined at 400°C in a muffle furnace in an air atmosphere for 4 hours to obtain a 25Cu / a-ZrOx material;
[0057] S7, at 25°C, take 0.5g of the above 25Cu / a-ZrOx material, disperse it in 50mL of water under ultrasonic conditions at a frequency of 50KHz for 15min to obtain a copper-zirconium composite oxide aqueous dispersion with a mass concentration of 10g / L; at 25°C, dissolve ammonium bicarbonate in water to form an ammonium bicarbonate aqueous solution with a mass concentration of 9.6g / L; the water is deionized water;
[0058] S8, taking the zirconium oxide aqueous dispersion, adding 0.537 g of ferric sulfate, stirring at 25° C. and 400 rpm for a fourth contact reaction for 1 hour; the molar ratio of the ammonium bicarbonate to the ferric sulfate calculated as Fe is 2:1;
[0059] S9, adding the aqueous solution of ammonium bicarbonate at 80°C, stirring for the fifth contact reaction for 3 hours; after the reaction is completed, the obtained material is fully washed and centrifuged at 6000-8000 rpm, the precipitate obtained after centrifugation is dried at 60°C for 12 hours and then crushed; calcining in a muffle furnace at 400°C in an air atmosphere for 4 hours to obtain a brown-black 15Fe / 25Cu / a-ZrO x Catalytic materials.
[0060] Example 2
[0061] A method for preparing a high-performance alkali metal-modified CuFeZr catalyst material comprises the following steps:
[0062] S1, at 25° C., 4.5036 g of zirconium oxychloride octahydrate was dissolved in ethanol to obtain a mixture, and after ultrasonic dissolution at a frequency of 40 KHz for 45 min, propylene oxide was added to carry out a first contact reaction for 10 min to obtain a solution I;
[0063] S2, performing a hydrothermal reaction at 150°C for 24 hours, drying the obtained solid sol at 60°C for 28 hours, and then drying at 200°C for 6 hours before crushing to obtain a powdery amorphous zirconium oxide solid; in terms of molar ratio, the amount of zirconium oxychloride: ethanol: propylene oxide is 1:70:2.5;
[0064] S3, at 25°C, 0.3 g of amorphous zirconium oxide solid is dispersed in 50 mL of water under ultrasonic conditions at a frequency of 45 KHz for 15 min to obtain a zirconium oxide aqueous dispersion with a mass concentration of 6 g / L; the water is deionized water;
[0065] S4, at 25°C, dissolving sodium carbonate in water to form a sodium carbonate aqueous solution with a mass concentration of 9.6 g / L;
[0066] S5, taking the zirconium oxide aqueous dispersion, adding 0.2949 g of copper sulfate pentahydrate, stirring at 25° C. and 350 rpm for a second contact reaction for 1.5 hours; the molar ratio of the sodium carbonate to the copper sulfate pentahydrate calculated as Cu is 2.5:1;
[0067] S6, adding the sodium carbonate aqueous solution at 80° C. and stirring for a third contact reaction for 5 hours; after the reaction is completed, the obtained material is fully washed and centrifuged at 6000-8000 rpm, the precipitate obtained after centrifugation is dried at 60° C. for 12 hours, crushed, and calcined at 400° C. in a muffle furnace in an air atmosphere for 4 hours to obtain a 25Cu / a-ZrOx material;
[0068] S7, at 25°C, take 0.5g of the above 25Cu / a-ZrOx material, disperse it in 50mL of water under ultrasonic conditions at a frequency of 50KHz for 15min to obtain a copper-zirconium composite oxide aqueous dispersion with a mass concentration of 10g / L; at 25°C, dissolve sodium bicarbonate in water to form a sodium bicarbonate aqueous solution with a mass concentration of 9.6g / L; the water is deionized water;
[0069] S8, taking the copper-zirconium composite oxide aqueous dispersion, adding 0.2086 g of ferric acetate, stirring at 25° C. and 400 rpm for a fourth contact reaction for 1 hour; the molar ratio of the sodium bicarbonate to the ferric acetate calculated as Fe is 3:1;
[0070] S9, adding the sodium bicarbonate aqueous solution at 80° C. and stirring for the fifth contact reaction for 3 hours; after the reaction is completed, the obtained material is fully washed and centrifuged at 6000-8000 rpm, and the precipitate obtained after centrifugation is dried at 60° C. for 12 hours and then crushed;
[0071] S10, add 24.7 mg of sodium carbonate to 1 mL of aqueous solution at 25° C., stir at 400 rpm at 25° C. for the sixth contact reaction for 2 h, then dry at 40-70° C. for 2-6 h in a rotary evaporator with a vacuum degree of -0.08 to -0.1, and calcine in a muffle furnace at 400° C. in an air atmosphere for 4 h to obtain a brown-black 3Na-10Fe / 25Cu / a-ZrOx catalytic material.
[0072] Example 3
[0073] A method for preparing a high-performance alkali metal-modified CuFeZr catalyst material comprises the following steps:
[0074] S1, at 25°C, 3.2569 g of zirconium chloride was dissolved in ethanol to obtain a mixture, and after ultrasonic dissolution for 45 min at a frequency of 30 KHz, propylene oxide was added to carry out a first contact reaction for 8 min to obtain a solution I;
[0075] S2, performing a hydrothermal reaction at 150°C for 16 hours, drying the obtained solid sol at 60°C for 24 hours, and then drying at 200°C for 3 hours before crushing to obtain a powdery amorphous zirconium oxide solid; in terms of molar ratio, the amount of zirconium chloride: ethanol: propylene oxide is 1:65:2;
[0076] S3, at 25°C, 0.3 g of amorphous zirconium oxide solid is dispersed in 50 mL of water under ultrasonic conditions at a frequency of 45 KHz for 15 min to obtain a zirconium oxide aqueous dispersion with a mass concentration of 6 g / L; the water is deionized water;
[0077] S4, at 25°C, dissolving sodium bicarbonate in water to form a sodium bicarbonate aqueous solution with a mass concentration of 9.6 g / L;
[0078] S5, taking the zirconium oxide aqueous dispersion, adding 0.1588 g of copper chloride, stirring at 400 rpm for a second contact reaction at 25° C. for 1 hour; the molar ratio of the sodium bicarbonate to the copper chloride calculated as Cu is 2:1;
[0079] S6, adding the sodium bicarbonate aqueous solution at 80° C. and stirring for a third contact reaction for 5 hours; after the reaction is completed, the obtained material is fully washed and centrifuged at 6000-8000 rpm, the precipitate obtained after centrifugation is dried at 60° C. for 12 hours, crushed, and calcined at 400° C. in a muffle furnace in an air atmosphere for 4 hours to obtain a 25Cu / a-ZrOx material;
[0080] S7, at 25°C, take 0.5g of the above 25Cu / a-ZrOx material, disperse it in 50mL of water under ultrasonic conditions at a frequency of 50KHz for 15min to obtain a copper-zirconium composite oxide aqueous dispersion with a mass concentration of 10g / L; at 25°C, dissolve potassium hydroxide in water to form a potassium hydroxide aqueous solution with a mass concentration of 9.6g / L; the water is deionized water;
[0081] S8, taking the copper-zirconium composite oxide aqueous dispersion, adding 0.2182 g of ferric chloride, stirring at 25° C. and 400 rpm for a fourth contact reaction for 1 hour; the molar ratio of potassium hydroxide to ferric chloride calculated as Fe is 2.5:1;
[0082] S9, adding the potassium hydroxide aqueous solution at 80° C. and stirring for a fifth contact reaction for 3 hours; after the reaction is completed, the obtained material is fully washed and centrifuged at 6000-8000 rpm, and the precipitate obtained after centrifugation is dried at 60° C. for 12 hours and then crushed;
[0083] S10, add 32.2 mg potassium carbonate 1 mL aqueous solution at 25 ° C, stir at 400 rpm for the sixth contact reaction at 25 ° C for 2 hours, then dry at 40-70 ° C for 2-6 hours in a rotary evaporator with a vacuum degree of -0.08 to -0.1, and calcine in a muffle furnace at 400 ° C for 4 hours in an air atmosphere to obtain a brown-black 3K-15Fe / 25Cu / a-ZrOx catalytic material.
[0084] Example 4
[0085] A method for preparing a high-performance alkali metal-modified CuFeZr catalyst material comprises the following steps:
[0086] S1, at 25°C, 3.96 g of zirconium sulfate was dissolved in ethanol to obtain a mixture, and after ultrasonic dissolution for 30 min at a frequency of 50 KHz, propylene oxide was added to carry out a first contact reaction for 6 min to obtain a solution I;
[0087] S2, performing a hydrothermal reaction at 150°C for 20 hours, drying the obtained solid sol at 60°C for 24 hours, and then drying at 200°C for 3 hours before crushing to obtain a powdery amorphous zirconium oxide solid; in terms of molar ratio, the amount of zirconium sulfate: ethanol: propylene oxide is 1:60:1.5;
[0088] S3, at 25°C, 0.3 g of amorphous zirconium oxide solid is dispersed in 50 mL of water under ultrasonic conditions at a frequency of 45 KHz for 15 min to obtain a zirconium oxide aqueous dispersion with a mass concentration of 6 g / L; the water is deionized water;
[0089] S4, at 25°C, dissolving sodium hydroxide in water to form a sodium hydroxide aqueous solution with a mass concentration of 9.6 g / L;
[0090] S5, taking the zirconium oxide aqueous dispersion, adding 0.2358 g of copper acetate monohydrate, stirring at 400 rpm for a second contact reaction at 25° C. for 1 hour; the molar ratio of the sodium hydroxide to the copper acetate monohydrate calculated as Cu is 3:1;
[0091] S6, adding the sodium hydroxide aqueous solution at 80° C. and stirring for a third contact reaction for 3 hours; after the reaction is completed, the obtained material is fully washed and centrifuged at 6000-8000 rpm, the precipitate obtained after centrifugation is dried at 60° C. for 12 hours, crushed, and calcined at 400° C. in a muffle furnace in an air atmosphere for 4 hours to obtain a 25Cu / a-ZrOx material;
[0092] S7, at 25°C, take 0.5g of the above 25Cu / a-ZrOx material, disperse it in 50mL of water under ultrasonic conditions of 50KHz for 15min to obtain a copper-zirconium composite oxide aqueous dispersion with a mass concentration of 10g / L; the water is deionized water;
[0093] S8, taking the copper-zirconium composite oxide aqueous dispersion, adding 0.7235 g of ferric nitrate nonahydrate, stirring at 25° C. and 400 rpm for a fourth contact reaction for 1 hour; the molar ratio of the ammonia water to the ferric nitrate nonahydrate calculated as Fe is 1:1;
[0094] S9, adding the ammonia solution at 80° C. and stirring for the fifth contact reaction for 3 hours; after the reaction is completed, the obtained material is fully washed and centrifuged at 6000-8000 rpm, and the precipitate obtained after centrifugation is dried at 60° C. for 12 hours and then crushed;
[0095] S10, add 75.9 mg of cesium carbonate and 1 mL of aqueous solution at 25° C., stir at 400 rpm for the sixth contact reaction at 25° C. for 2 h, then dry at 40-70° C. for 2-6 h in a rotary evaporator with a vacuum degree of -0.08 to -0.1, and calcine in a muffle furnace in an air atmosphere at 400° C. for 4 h to obtain a brown-black 3Cs-20Fe / 25Cu / a-ZrOx catalytic material.
[0096] Example 5
[0097] A method for preparing a high-performance alkali metal-modified CuFeZr catalyst material comprises the following steps:
[0098] S1, at 25° C., 5.999 g of zirconium nitrate pentahydrate was dissolved in ethanol to obtain a mixture, and after ultrasonic dissolution at a frequency of 50 KHz for 30 min, propylene oxide was added to carry out a first contact reaction for 4 min to obtain a solution I;
[0099] S2, performing a hydrothermal reaction at 150°C for 20 hours, drying the obtained solid sol at 60°C for 24 hours, and then drying at 200°C for 3 hours before crushing to obtain a powdery amorphous zirconium oxide solid; in terms of molar ratio, the amount of zirconium nitrate pentahydrate: ethanol: propylene oxide is 1:60:1.5;
[0100] S3, at 25°C, 0.3 g of amorphous zirconium oxide solid is dispersed in 50 mL of water under ultrasonic conditions at a frequency of 45 KHz for 15 min to obtain a zirconium oxide aqueous dispersion with a mass concentration of 6 g / L; the water is deionized water;
[0101] S4, at 25°C, dissolving ammonium carbonate in water to form an ammonium carbonate aqueous solution with a mass concentration of 9.6 g / L;
[0102] S5, taking the zirconium oxide aqueous dispersion, adding 0.2358 g of copper acetate monohydrate, stirring at 400 rpm for a second contact reaction at 25° C. for 1 hour; the molar ratio of the ammonium carbonate to the copper acetate monohydrate calculated as Cu is 1:1;
[0103] S6, adding the aqueous solution of ammonium carbonate at 80°C, stirring for a third contact reaction for 3 hours; after the reaction is completed, the obtained material is fully washed and centrifuged at 6000-8000 rpm, the precipitate obtained after centrifugation is dried at 60°C for 12 hours, crushed, and calcined at 400°C in a muffle furnace in an air atmosphere for 4 hours to obtain a 25Cu / a-ZrOx material;
[0104] S7, at 25°C, take 0.5g of the above 25Cu / a-ZrOx material, disperse it in 50mL of water under ultrasonic conditions of 50KHz for 15min to obtain a copper-zirconium composite oxide aqueous dispersion with a mass concentration of 10g / L; the water is deionized water;
[0105] S8, taking the copper-zirconium composite oxide aqueous dispersion, adding 0.5426 g of ferric nitrate nonahydrate, stirring at 25° C. and 400 rpm for a fourth contact reaction for 1 hour; the molar ratio of the ammonium carbonate to the ferric nitrate nonahydrate calculated as Fe is 2:1;
[0106] S9, adding the aqueous ammonium carbonate solution at 80° C. and stirring for a fifth contact reaction for 3 hours; after the reaction is completed, the obtained material is fully washed and centrifuged at 6000-8000 rpm, and the precipitate obtained after centrifugation is dried at 60° C. for 12 hours and then crushed;
[0107] S10, add 42.9 mg potassium carbonate and 1 mL aqueous solution at 25°C, stir at 400 rpm for the sixth contact reaction at 25°C for 2 hours, then dry at 40-70°C for 2-6 hours in a rotary evaporator with a vacuum degree of -0.08 to -0.1, and calcine in a muffle furnace at 400°C in an air atmosphere for 4 hours to obtain a brown-black 4K-15Fe / 25Cu / a-ZrOx catalytic material.
[0108] Example 6
[0109] A method for preparing a high-performance alkali metal-modified CuFeZr catalyst material comprises the following steps:
[0110] S1, at 25° C., 5.999 g of zirconium nitrate pentahydrate was dissolved in ethanol to obtain a mixture, and after ultrasonic dissolution for 30 min at a frequency of 50 KHz, propylene oxide was added to carry out a first contact reaction for 2 min to obtain a solution I;
[0111] S2, performing a hydrothermal reaction at 150°C for 20 hours, drying the obtained solid sol at 60°C for 24 hours, and then drying at 200°C for 3 hours before crushing to obtain a powdery amorphous zirconium oxide solid; in terms of molar ratio, the amount of zirconium nitrate pentahydrate: ethanol: propylene oxide is 1:60:1.5;
[0112] S3, at 25°C, 0.3 g of amorphous zirconium oxide solid is dispersed in 50 mL of water under ultrasonic conditions at a frequency of 45 KHz for 15 min to obtain a zirconium oxide aqueous dispersion with a mass concentration of 6 g / L; the water is deionized water;
[0113] S4, at 25°C, dissolving ammonium carbonate in water to form an ammonium carbonate aqueous solution with a mass concentration of 9.6 g / L;
[0114] S5, taking the zirconium oxide aqueous dispersion, adding 0.2358 g of copper acetate monohydrate, stirring at 400 rpm for a second contact reaction at 25° C. for 1 hour; the molar ratio of the ammonium carbonate to the copper acetate monohydrate in terms of Cu is 1.5:1;
[0115] S6, adding the aqueous solution of ammonium carbonate at 80°C, stirring for a third contact reaction for 3 hours; after the reaction is completed, the obtained material is fully washed and centrifuged at 6000-8000 rpm, the precipitate obtained after centrifugation is dried at 60°C for 12 hours, crushed, and calcined at 400°C in a muffle furnace in an air atmosphere for 4 hours to obtain a 25Cu / a-ZrOx material;
[0116] S7, at 25°C, take 0.5g of the above 25Cu / a-ZrOx material, disperse it in 50mL of water under ultrasonic conditions of 50KHz for 15min to obtain a copper-zirconium composite oxide aqueous dispersion with a mass concentration of 10g / L; the water is deionized water;
[0117] S8, taking the copper-zirconium composite oxide aqueous dispersion, adding 0.5426 g of ferric nitrate nonahydrate, stirring at 25° C. and 400 rpm for a fourth contact reaction for 1 hour; the molar ratio of the ammonium carbonate to the ferric nitrate nonahydrate calculated as Fe is 2.5:1;
[0118] S9, adding the aqueous ammonium carbonate solution at 80° C. and stirring for a fifth contact reaction for 3 hours; after the reaction is completed, the obtained material is fully washed and centrifuged at 6000-8000 rpm, and the precipitate obtained after centrifugation is dried at 60° C. for 12 hours and then crushed;
[0119] S10, add 53.7 mg potassium carbonate and 1 mL aqueous solution at 25°C, stir at 400 rpm for the sixth contact reaction at 25°C for 2 hours, then dry at 40-70°C for 2-6 hours in a rotary evaporator with a vacuum degree of -0.08 to -0.1, and calcine in a muffle furnace at 400°C in an air atmosphere for 4 hours to obtain a brown-black 5K-15Fe / 25Cu / a-ZrOx catalytic material.
[0120] Example 7
[0121] A method for preparing a high-performance alkali metal-modified CuFeZr catalyst material comprises the following steps:
[0122] S1, at 25° C., 5.999 g of zirconium nitrate pentahydrate was dissolved in ethanol to obtain a mixture, and after ultrasonic dissolution for 30 min at a frequency of 50 KHz, propylene oxide was added to carry out a first contact reaction for 2 min to obtain a solution I;
[0123] S2, performing a hydrothermal reaction at 150°C for 20 hours, drying the obtained solid sol at 60°C for 24 hours, and then drying at 200°C for 3 hours before crushing to obtain a powdery amorphous zirconium oxide solid; in terms of molar ratio, the amount of zirconium nitrate pentahydrate: ethanol: propylene oxide is 1:60:1.5;
[0124] S3, at 25°C, 0.3 g of amorphous zirconium oxide solid is dispersed in 50 mL of water under ultrasonic conditions at a frequency of 45 KHz for 15 min to obtain a zirconium oxide aqueous dispersion with a mass concentration of 6 g / L; the water is deionized water;
[0125] S4, at 25°C, dissolving ammonium carbonate in water to form an ammonium carbonate aqueous solution with a mass concentration of 9.6 g / L;
[0126] S5, taking the zirconium oxide aqueous dispersion, adding 0.1886 g of copper acetate monohydrate, stirring at 400 rpm for a second contact reaction at 25° C. for 1 hour; the molar ratio of the ammonium carbonate to the copper acetate monohydrate calculated as Cu is 1.5:1;
[0127] S6, adding the aqueous ammonium carbonate solution at 80°C, stirring for a third contact reaction for 3 hours; after the reaction is completed, the obtained material is fully washed and centrifuged at 6000-8000 rpm, the precipitate obtained after centrifugation is dried at 60°C for 12 hours, crushed, and calcined at 400°C in a muffle furnace in an air atmosphere for 4 hours to obtain a 20Cu / a-ZrOx material;
[0128] S7, at 25°C, take 0.5g of the above 20Cu / a-ZrOx material, disperse it in 50mL of water under ultrasonic conditions of 50KHz for 15min to obtain a copper-zirconium composite oxide aqueous dispersion with a mass concentration of 10g / L; the water is deionized water;
[0129] S8, taking the copper-zirconium composite oxide aqueous dispersion, adding 0.5426 g of ferric nitrate nonahydrate, stirring at 25° C. and 400 rpm for a fourth contact reaction for 1 hour; the molar ratio of the ammonium carbonate to the ferric nitrate nonahydrate calculated as Fe is 1.5:1;
[0130] S9, adding the aqueous ammonium carbonate solution at 80° C. and stirring for a fifth contact reaction for 3 hours; after the reaction is completed, the obtained material is fully washed and centrifuged at 6000-8000 rpm, and the precipitate obtained after centrifugation is dried at 60° C. for 12 hours and then crushed;
[0131] S10, add 32.2 mg potassium carbonate 1 mL aqueous solution at 25 ° C, stir at 400 rpm at 25 ° C for the sixth contact reaction for 2 hours, then dry at 40-70 ° C for 2-6 hours in a rotary evaporator with a vacuum degree of -0.08 to -0.1, and calcine in a muffle furnace at 400 ° C for 4 hours in an air atmosphere to obtain a brown-black 3K-15Fe / 20Cu / a-ZrOx catalytic material.
[0132] Test Example 1
[0133] The catalysts of the above examples were tested to obtain specific surface area and pore size.
[0134] The specific surface area was obtained by testing with Micromeritics ASAP-2010; the pore size was obtained by testing with Micromeritics ASAP-2010.
[0135] The results are shown in Table 1.
[0136] Table 1 Test results of specific surface area of catalytic materials obtained in Examples 1 to 6
[0137]
[0138]
[0139] As can be seen from Table 1, the alkali metal modified CuFeZr catalytic material prepared by the present invention has a specific surface area of 35-88m 2 / g, which can effectively increase the stability of active metal / interface species, improve the ability of catalytic dissociation of hydrogen and activation of carbon dioxide, and is beneficial to the hydrogenation of carbon dioxide to produce low-carbon alcohols.
[0140] Test Example 2
[0141] The catalysts of the above examples were used to perform catalytic hydrogenation of CO2 gas to produce low-carbon alcohols. The flow rate of the CO2+H2 mixed gas was 36.0 mL / min (4 vol% N2, 24 vol% CO2, 72 vol% H2) and the space velocity was 3000 mL / (g cat ·h) Establish a micro fixed bed simulation reaction system. First, before the activity test, 0.4g of the sample was reduced in a 10vol% H2 / Ar gas flow at 320°C for 1h, and then the CO2+H2+N2 mixed reactants were introduced and pressurized to 5MPa. Subsequently, the catalytic performance was evaluated at different target temperatures (280, 300 and 320°C). The obtained tail gas components such as CO, CO2, methanol, C2-C5 low-carbon alcohols, C2-C8 olefins and C1-C8 alkanes were quantitatively analyzed online by a gas chromatograph with a thermal conductivity detector and a flame ionization detector to obtain the data in Tables 2, 3 and 4. In addition, after changing the mass ratio of Cu / Zr, the 3K-15Fe / 20Cu / a-ZrOx catalyst also achieved a CO2 conversion rate of 30.9%, 21.6% and 46.1mg.g at 320°C. cat -1 h -1 Selectivity and yield of low-carbon alcohols.
[0142] Table 2: Temperature is 280℃
[0143]
[0144]
[0145] Table 3: Temperature is 300℃
[0146]
[0147] Table 4: Temperature is 320℃
[0148]
[0149]
[0150] It can be seen from the above results that the catalytic material of the present invention has excellent carbon dioxide conversion rate and low-carbon alcohol selectivity / yield, reflecting excellent catalytic performance for preparing low-carbon alcohols by hydrogenation of carbon dioxide.
[0151] Test Example 3
[0152] The products obtained in the above Examples 1-6 were subjected to X-ray powder diffraction (XRD) experiments on a Miniflex 600 XRD diffractometer manufactured by Rigaku. The results are as follows: Figure 1 as shown in .
[0153] Depend on Figure 1 It can be seen that after doping with copper, iron and alkali metal K, the amorphous structure of the catalyst carrier is still maintained, and the crystalline phase peak metals of metallic copper, iron, potassium and their oxides are not detected. This shows that amorphous zirconia with a high specific surface area is conducive to the high dispersion of active metals and the formation of tiny-sized copper, iron, potassium nanocrystals or their rich alloy interface species, which significantly improves the material's performance in catalytic hydrogenation of CO2 to produce low-carbon alcohols.
[0154] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. Application of a high-performance alkali metal-modified CuFeZr catalytic material, characterized in that: The preparation method of the high-performance alkali metal-modified CuFeZr catalyst material comprises the following steps: S1, adding zirconium salt to ethanol solvent, dissolving by ultrasonication, and then adding propylene oxide to carry out a first contact reaction to obtain solution I; the molar ratio of propylene oxide to zirconium salt calculated as Zr element is (1.5-2.5):1; S2, subjecting solution I to a hydrothermal reaction, and drying and crushing the resulting material to obtain amorphous zirconium oxide; S3, adding amorphous zirconium oxide to water, dispersing by ultrasonic, adding copper salt, performing a second contact reaction, and obtaining a solution II; the mass ratio of the copper salt calculated as Cu element to the amorphous zirconium oxide calculated as zirconium oxide is (0.2-0.3):1; S4, adding a precipitant aqueous solution to solution II to carry out a third contact reaction. After the reaction is completed, the obtained material is centrifuged, dried, crushed, and calcined to obtain a copper-zirconium material; the molar ratio of the precipitant to the copper salt calculated as Cu element is (1-3); S5, subjecting the obtained solid to a fourth contact reaction with an iron salt to obtain a solution III; the mass ratio of the iron salt to the copper-zirconium material calculated as Fe element is (0.1-0.2):1; S6, subjecting the solution III to a fifth contact reaction with a precipitant, and after the reaction is completed, centrifuging, drying, and crushing the resulting material; the molar ratio of the precipitant to the copper salt calculated as Fe element is (1-3); S7, the obtained material is subjected to a sixth contact reaction with an alkali metal salt, after rotary evaporation to dry the water, the obtained material is crushed and calcined to obtain a high-performance alkali metal-modified CuFeZr catalytic material; the molar ratio of the alkali metal salt calculated as the alkali metal element to the amorphous zirconia calculated as the Zr element is (0.10-0.25):1; The high-performance alkali metal-modified CuFeZr catalytic material is used for catalytic reduction of CO2 to synthesize low-carbon alcohols, and the low-carbon alcohols are alcohol compounds composed of 2 to 5 carbon atoms.
2. The use of the high-performance alkali metal-modified CuFeZr catalytic material according to claim 1, characterized in that: In step S1, the zirconium salt is one of zirconium nitrate, zirconium oxychloride, zirconium chloride and zirconium sulfate.
3. The use according to claim 1, characterized in that: The conditions of the first contact reaction are: temperature of 10-40°C and time of 0.05-1h; The first contact reaction is carried out under stirring, and the stirring rate is 50-500 rpm.
4. The use according to claim 1, characterized in that: In step S2, the temperature of the hydrothermal reaction is 100-200°C and the time is 15-25h.
5. The use according to claim 1, characterized in that: In step S3, the conditions of the second contact reaction are: temperature of 10-40° C., time of 0.05-10 h; The copper salt is any one of copper nitrate, copper sulfate, copper acetate and copper chloride; The second contact reaction is carried out under stirring, and the stirring rate is 50-500 rpm.
6. The use according to claim 1, characterized in that: In step S4, the conditions of the third contact reaction are: temperature of 70-90° C., time of 0.1-10 h; The precipitant is any one of ammonium carbonate, ammonium bicarbonate, potassium carbonate, potassium bicarbonate, sodium carbonate, sodium bicarbonate, sodium hydroxide, potassium hydroxide, and ammonia water.
7. The use according to claim 1, characterized in that: In step S2, the drying conditions are: temperature of 60-100°C and time of 4-24h.
8. The use according to claim 1, characterized in that: In step S4, the drying conditions include: temperature of 40-80°C, time of 4-24h; the calcination conditions include: temperature of 300-500°C, time of 3-10h.
9. The use according to claim 1, characterized in that: In step S5, the conditions of the fourth contact reaction are: temperature of 10-40° C., time of 0.05-10 h; The iron salt is any one of ferric nitrate, ferric acetate, ferric sulfate and ferric chloride; The fourth contact reaction is carried out under stirring, and the stirring rate is 50-500 rpm.
10. The use according to claim 1, characterized in that: In step S6, the conditions of the fifth contact reaction are: temperature of 70-90° C., time of 0.1-10 h; The precipitant is any one of ammonium carbonate, ammonium bicarbonate, potassium carbonate, potassium bicarbonate, sodium carbonate, sodium bicarbonate, sodium hydroxide, potassium hydroxide, and ammonia water.
11. The use according to claim 1, characterized in that: In step S6, the drying conditions include: temperature of 40-80°C and time of 4-24h.
12. The use according to claim 1, characterized in that: In step S7, the conditions of the sixth contact reaction are: temperature of 10-50° C., time of 2-10 h; The alkali metal salt is any one of potassium carbonate, sodium carbonate and cesium carbonate; The sixth contact reaction is carried out under stirring, and the stirring rate is 50-500 rpm.
13. The use according to claim 1, characterized in that: In step S7, the conditions for the rotary evaporation include: a temperature of 40-80°C, a vacuum degree of -0.08 to -0.1, and a time of 2-6 hours; the conditions for the calcination include: a temperature of 300-500°C and a time of 3-10 hours.
Citation Information
Patent Citations
Zirconium-based arsenic removing material and preparation method and application thereof
CN102068957A